2016
DOI: 10.18203/2349-3291.ijcp20164591
|View full text |Cite
|
Sign up to set email alerts
|

Validation of language evaluation scale Trivandrum in children aged 3 -6 years attending well baby clinic in a tertiary care hospital

Abstract: Background: Delay in language development is often an early and most sensitive indicator of intellectual disability. Language delay should be detected in early stages for early intervention, so our study is to validate a simple screening tool to assess language and speech delay in a tertiary care setting. Present study was conducted to validate LEST to use in pediatric clinics to identify delay in language development among children of 3-6years, and to compare LEST and extended receptive expressive emergent sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…A study conducted on the LEST scale on children aged three to six years by Singaraiah et al found that boys had a significantly higher language delay than girls, with a male-to-female ratio of 2.2:1 [ 6 ] The male-to-female ratio in the study by Nair et al was 1.3:1 [ 7 ]. Our study revealed a male-to-female ratio of 2:1, which was in line with the findings of Singaraiah et al [ 6 ] and Krogh et al [ 5 ] who used Bailey 3 scores and demonstrated gender differences in test scores; however, the pattern of the differences varied across scales and subtests.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study conducted on the LEST scale on children aged three to six years by Singaraiah et al found that boys had a significantly higher language delay than girls, with a male-to-female ratio of 2.2:1 [ 6 ] The male-to-female ratio in the study by Nair et al was 1.3:1 [ 7 ]. Our study revealed a male-to-female ratio of 2:1, which was in line with the findings of Singaraiah et al [ 6 ] and Krogh et al [ 5 ] who used Bailey 3 scores and demonstrated gender differences in test scores; however, the pattern of the differences varied across scales and subtests.…”
Section: Discussionmentioning
confidence: 99%
“…Nair et al developed the LEST which was initially validated in young children (zero to three years old). It has been acknowledged as one of the best screening tools for identifying language and speech delays in a community context [ 6 ]. A total of 33 test items were selected from the list of items created from the pilot studies conducted among children aged zero to one year, one to two years, and two to three years.…”
Section: Introductionmentioning
confidence: 99%